The Effects of Neurolinguistic Programming (NlP) Methods Towards Students’ Speaking Skill - Mildan Arsdan Fidinillah (Scope : Journal of English Language Teaching, 2018)
The objective of this research is to investigate the effects of Neurolinguistic Programming (NLP) method towards students’ speaking skill at Madrasah Ibtidaiyah Sa’adatuddarain 2 Tangerang Selatan. This research was conducted at Madrasah Ibtidaiyah Sa’adatuddarain 2 Tangerang Selatan from April 15th 2016-July 15th 2016.  By using purposive sampling technique, 60 out of 300 students of grade V in school year 2015-2016 were chosen. The method used was a survey with a correlational technique. The instrument included one test to analyze the data quantitatively.  Test is used to assess the students’ speaking skill.  There is a positive and significant impact of students that learning using NLP method in the ability of speaking English. Furthermore, ? = 0.05, df = 19, and t-table = 1.73, while tcount = 9, 26. Thus tcount> ttable, this means that H0is rejected and H1is accepted, As conclusion, NLP method affects positively and significantly to the students’ speaking English ability compared with conventional method. Key words: Neurolinguistic Programming (NLP) method, speaking skill, English learning